A Multimodal, Longitudinal Investigation of Alcohol’s Emotional Rewards and Drinking over Time in Young Adults - Venerable, Walter J. (Psychol Addict Behav, 2020)
Theories of Alcohol Use Disorder (AUD) have long suggested that alcohol’s emotional rewards play a key role in reinforcing problematic drinking. Studies employing survey methods, in which participants recall and aggregate their experiences with alcohol in a single questionnaire, indicate that self-reported expectancies and motivations surrounding alcohol’s emotional rewards predict problematic drinking trajectories over time. The current study is the first to combine laboratory alcohol-administration, ambulatory methods, and longitudinal follow-ups to assess whether alcohol’s ability to enhance positive mood and reduce negative mood predicts later drinking problems. Sixty young heavy social drinkers (50% female) participated in laboratory-based alcohol-administration, attending both alcohol (target BAC .08%) and no-alcohol laboratory sessions. Forty-eight of these participants also wore transdermal alcohol monitors and completed mood surveys outside the laboratory for 7-days. Participants reported on their drinking at 18-month follow-up (90% compliance). Controlling for baseline drinking, greater negative mood reduction from alcohol at baseline predicted more drinking problems at follow-up, an effect that emerged as consistent across methods capturing alcohol’s emotional rewards in the laboratory, b=−.24, p=.02, as well as via ambulatory methods, b=−3.14, p=.01. Greater positive mood enhancement from alcohol, captured via laboratory methods, also predicted drinking problems, b=.16, p=.03, and binge drinking, b= 3.22, p=.02, at follow-up. Models examining drinking frequency/quantity were non-significant. Results provide support for emotional reward as a potential factor in the development of problematic drinking.